Analisis Pengaruh Gender pada Kemiskinan Indonesia Tahun 2018 - 2023 - Citra Ayu Aprianing; Suharno Suharno (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Poverty is a problem experienced by all countries including Indonesia, Indonesia has a percentage of poor people reaching 8% - 12% from 2010 to 2024. The percentage of poor people in Indonesia which is more than 5% for 14 years shows that Indonesia still has many poor people, one of which is influenced by gender discrimination. This study aims to analyze the influence of gender on poverty in Indonesia in 2018 - 2023. This research method uses quantitative data, panel data from 34 provinces in Indonesia and uses Multiple Linear Regression analysis tools with independent variables being the Female Labor Force Participation Rate (TPAKP), Women's Human Development Index (IPMP) and GRDP. The results of the study (1) Overall TPAKP, IPMP and GRDP have an effect on poverty; (2) TPAKP has a significant positive effect on poverty; (3) IPMP has a significant negative effect on poverty; (4) GRDP has a negative but insignificant effect on poverty.